Measurement Stand and Methodology for Research of the Off-Body and Body-to-Body Radio Channels in WBANs with Different Diversity Schemes - Slawomir J. Ambroziak (International Journal of Antennas and Propagation)
The concept of an experimental test bed for system loss and channel impulse response measurements for off-body and body-to-body radio channels in wireless body area networks (WBANs) is fully described. The possible measurement scenarios that may occur in investigation of off-body and body-to-body channels are classified and described in detail. Additionally, an evaluation is provided of the standard and expanded uncertainties of the presented measurement stand and methodology. Finally, the exemplary results are presented and discussed, in order to point out the need for further investigations of different diversity schemes and their applications in WBANs.